ألفاظ اللغات غير العربية في القرآن الكريم من منظور الدراسات اللغوية الحديثة = Alfaz al-lughat ghyr a-'Arabiyah fi al-Qur'an al-Karim min manzur al-dirasat al-lughawiyah al-hadithah - Kheir , Abdalla Mohamed Adam; El-Mesawi, Mohamed El-Tahir; Omar, Zakaria (IIUM Press, 2014)
Language scholars agree that there is mutual influence among languages,thus each language borrowing what it needs from other languages and supplying them with what they need in terms of words and vocabulary. Like other nations, the Arabs had specific experience in linguistic exchange through their intercourse with other nations both by virtue of neighbourhood and due to their regular winter and summer trade journeys to regions far away from the Arabian Peninsula. This resulted in the reception by the Arabic language of vocabulary and words from other languages,conventionally known as loanwords and Arabized vocabulary. This fact, notwithstanding, scholars have differed on the occurrence of such borrowed and Arabized words in the Qur’an. The present article addresses this issue through applying a descriptive and analytical method in examining the different opinions held by classical Islamic scholars and Qur’an commentators in light of modern linguistic studies. Key words: Arabic language, linguistic exchange, loanwords, Arabized vocabulary, Arabic language scholars, Qur’an commentators, modern linguistic studies.